2005
DOI: 10.1002/uog.2650
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional sonographic description of abnormal metopic suture in second‐ and third‐trimester fetuses

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 12 publications
2
48
0
7
Order By: Relevance
“…Chaoui et al [9] reported clear 3D images for the identification of an abnormally wide metopic suture in the second trimester of pregnancy. However, rapid ossification of the craniofacial bones occurs during the first trimester of pregnancy.…”
Section: Visualization Of Normal Embryomentioning
confidence: 99%
“…Chaoui et al [9] reported clear 3D images for the identification of an abnormally wide metopic suture in the second trimester of pregnancy. However, rapid ossification of the craniofacial bones occurs during the first trimester of pregnancy.…”
Section: Visualization Of Normal Embryomentioning
confidence: 99%
“…En la semana 32 existe un cierre aparente de la sutura metópica en la región supranasal y, posteriormente, el cierre se mueve hacia la fontanela anterior, por tanto el cierre de la sutura metópica ya se observa en el tercer trimestre. Chaoui et al (2005) confirmaron estos hallazgos, reportando que a las 32 semanas se observa el cierre aparente de la sutura metópica desde la glabela, extendiéndose superiormente hacia la fontanela anterior. Este patrón de desarrollo también se ha observado en fetos con trisomía 21, donde en los casos de ausencia de huesos nasales como consecuencia de la migra-ción y/o función defectuosa de las células de la cresta neural, no se afecta el desarrollo de los huesos frontales ni el cierre de la sutura metópica, ya que este déficit se limita al desarrollo de los huesos nasales (Faro et al, 2006).…”
Section: Discussionunclassified
“…Subsequently, development of the fetal forehead has been described in abnormal conditions including holoprosencephaly and Apert syndrome 2,3 . We report on an atypical case of Goldenhar syndrome, presenting prenatally with an additional cranial bone.…”
Section: Goldenhar Syndrome Presenting Atypically With An Additional mentioning
confidence: 99%
“…Chaoui et al 3 reported on 11 cases with abnormalities of the metopic suture, detected in the second and third trimesters of pregnancy. Among these fetuses, three had developed additional bones and all presented with additional abnormalities (intracranial, facial and extracranial); all pregnancies were terminated.…”
Section: Goldenhar Syndrome Presenting Atypically With An Additional mentioning
confidence: 99%